The Effectiveness Of Google Classroom and Dojo Class Using the Discovery Learning Model on The Learning Outcomes of Vocational School Students - Suswanto, Hary; Soraya, Dila Umnia; Ramadiani, Nanda Resta; Utomo, Wahyu Mulyo (Universitas Negeri Malang, 2022)
The aims of this study were to determine: (1) student learning outcomes through the use of Google Classroom and Class Dojo with the discovery learning model and (2) the effectiveness and efficiency of using Google Classroom and Class Dojo with the discovery learning model for class X. Multimedia students at SMKN 7 Poor. This research is a quasi-experimental research with quantitative and qualitative methods with the design of